Nutrients Status of Cultivated Soils of Ganga Canal Area of Meerut District of Uttar Pradesh - Kumar, Pramod; Kumar, Ashok; Kumar, Pardeep; Dhayni, B. P.; Shahi, U. P.; Kumar, Satendra; Kumar, Robin; Dwivedi, Ashish (International Journal of Bio-resource and Stress Management, 2016)
Incidence of nutrient deficiency in soils and plants has been reported worldwide including India. The present study was conducted to characterize their chemical properties and accordingly to develop optimum land use plan to realize maximum agricultural productivity. The surface (0–15 cm) and sub-surface (15–30) soil samples were collected from cultivated soils representing the six location of Meerut district namely, Kaili (Sakoti), Milak (Sardhana), Nanu (SP), Pooth (Rohata), Bhola (Jhal) and Jani, Meerut, Uttar Pradesh, India, respectively. The status of available macro, micro nutrient in soils and other soil properties like pH, electrical conductivity (EC) and organic carbon (OC) content were assessed. Results revealed that the soil of study area were neutral to strongly alkaline in reaction and non-saline in nature. Nutrient status regarding to the available macro and micro nutrient in surface (0–15 cm) and subsurface (15–30 cm) depth of soil indicate that soils are low in available N and medium in available P and K in surface and subsurface soil and in general sufficient in available Zn, Cu, Fe and Mn in the surface and subsurface layer of the soil. The Nutrient Index (NI) values were low for available nitrogen (1.16) and medium with respect to phosphorus (2.34) and potassium (1.91). in the soils of study area. A positive and significant correlation of NPK and micronutrients was found with organic matter content while significant and negative correlations exist between micronutrients and soil pH.